2014
DOI: 10.1093/schbul/sbt193
|View full text |Cite
|
Sign up to set email alerts
|

Partial Genetic Deletion of Neuregulin 1 Modulates the Effects of Stress on Sensorimotor Gating, Dendritic Morphology, and HPA Axis Activity in Adolescent Mice

Abstract: Stress has been linked to the pathogenesis of schizophrenia. Genetic variation in neuregulin 1 (NRG1) increases the risk of developing schizophrenia and may help predict which high-risk individuals will transition to psychosis. NRG1 also modulates sensorimotor gating, a schizophrenia endophenotype. We used an animal model to demonstrate that partial genetic deletion of Nrg1 interacts with stress to promote neurobehavioral deficits of relevance to schizophrenia. Nrg1 heterozygous (HET) mice displayed greater ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 112 publications
1
22
0
Order By: Relevance
“…The atypical effect of THC on Nrg1 HET mice appeared to be dependent on stress and correlated with increased activation of stress circuitry in the brain, with pronounced effects in the lateral septum (Boucher et al, 2007b). Interestingly, more recent studies reported that stress decreased expression of Nrg1 in the brain (Brydges et al, 2014; Makinodan et al, 2012), and partial genetic deletion of Nrg1 altered behavioural and neurobiological responses to stress (Chohan et al, 2014a; Chohan et al, 2014b; Desbonnet et al, 2012; Taylor et al, 2011). …”
Section: Individual Differences In Response To Cannabis: Contributmentioning
confidence: 99%
“…The atypical effect of THC on Nrg1 HET mice appeared to be dependent on stress and correlated with increased activation of stress circuitry in the brain, with pronounced effects in the lateral septum (Boucher et al, 2007b). Interestingly, more recent studies reported that stress decreased expression of Nrg1 in the brain (Brydges et al, 2014; Makinodan et al, 2012), and partial genetic deletion of Nrg1 altered behavioural and neurobiological responses to stress (Chohan et al, 2014a; Chohan et al, 2014b; Desbonnet et al, 2012; Taylor et al, 2011). …”
Section: Individual Differences In Response To Cannabis: Contributmentioning
confidence: 99%
“…Partial genetic deletion of Nrg1 conferred vulnerability to the effects of adolescent social defeat stress on spatial working memory function and modulation of inflammatory cytokines in the prefrontal cortex and hippocampus (Desbonnet et al, 2012 ). We have also recently shown that partial genetic deletion of Nrg1 altered neurobehavioral responses to repeated adolescent restraint stress (Chohan et al, 2014 ). Repeated adolescent stress selectively impaired the development of normal sensorimotor gating in Nrg1 heterozygous ( Nrg1 HET) mice which correlated with a dysregulation in stress-induced corticosterone release.…”
Section: Introductionmentioning
confidence: 85%
“…Male mice were subjected to 30 min/day of restraint stress for 14 days from PND 36 to PND 49 as described in our previous study (Chohan et al, 2014 ). Restraint stress was chosen as it is a well-characterized physical stressor in rodents that activates the HPA axis and increases anxiety-related behavior (Eiland and McEwen, 2010 ; Sutherland et al, 2010 ; Sutherland and Conti, 2011 ; Chesworth et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…Acute and repeated stress resulted in increased levels of corticosterone levels, however the response was significantly less in the mutants after repeated stress. Interestingly stress decreased apical dendritic length and complexity in the medial prefrontal cortex and hippocampus of the mutants (Chohan et al, 2014a). NMDA receptor binding of MK-801 was increased but the response was blunted in the ventrolateral septum, more pronounced in the dentate gyrus, and binding was decreased in the inferior-lateral region of the mPFC of the mutants (Chohan et al, 2014b).…”
Section: Gene-environment Interplaymentioning
confidence: 99%